Financial markets, banking, and monetary policy (Dubuque, IA : Kendall Hunt Publishing, 2018)
The Great Recession of 2007-2009 had a dramatic effect on the financial markets, the banking system, and the conduct of monetary policy. Financial Markets, Banking, and Monetary Policy takes the reader through the complexities of the credit crisis that led up to the Great Recession and its aftermath. A detailed description of the money markets, the corporate and Treasury bond markets, and the stock market, and how the financial assets in those markets are priced and traded is then provided. This text describes how the structure of the banking system had been undergoing significant changes since the early 1980s and how these changes are ongoing today. An account is given of how the Federal Reserve's unprecedented interventions in the financial markets served to quell the credit crisis and stabilize an otherwise fragile financial system, and how it must not impose an "exit strategy" to deal with the residual effects of its crisis management: a bloated balance sheet and interest rates near zero, that will take it to a "new normal."
Includes bibliographical references and indexes.
oif 22/01/2020
Loans
Keywords: Monetary policy; Banks and banking; Capital market; Finance